Using the cell phone while standing or walking affects balance and mobility in people with Parkinson's disease - Tayla Borges Lino; Milena Nunes de Oliveira da Silva; Isabela Corrêa de Paula; Sarah Jane Lemos de Melo; Suzi Rosa Miziara Barbosa; Gustavo Christofoletti (Arquivos de Neuro-Psiquiatria)
Background Cell phones are part of peoples' lives. The literature indicates risks when cell phones are used during a secondary motor task. Studies addressing this topic in people with Parkinson's disease are still scarce. Objective To investigate the impact of daily dual tasks with cell phone on balance and mobility in people with Parkinson's disease, compared to healthy control peers. Methods Participants with Parkinson's disease and controls underwent three motor tasks: (1) Standing and walking without using a cell phone; (2) Standing and walking while talking on the phone; and (3) Standing and walking while texting messages on the phone. Assessments involved balance and mobility tests. Statistical analysis was performed with multivariate analysis of variance, comparing main effect for group (Parkinson's disease × control), task (using × not using cell phone) and interactions (group × task). Significance was set at 5%. Effect sizes are reported. Results Participants with Parkinson's disease showed worse balance (p = 0.001, effect size of 0.471) and mobility (p = 0.001, effect size of 0.472) than control peers. The use of cell phone while performing a secondary motor task affected both groups (p = 0.005, effect size of 0.673 for balance and p = 0.001, effect size of 0.549 for mobility). The dual task impact, however, was higher in the Parkinson's disease group (p = 0.009, effect size of 0.407 for mobility). Conclusion Daily dual tasks with cell phones increase imbalance and mobility risks in Parkinson's disease. People should be careful when using their cell phone while standing or walking.